Long-period quasi-periodic oscillations of a small-scale magnetic structure on the Sun - D. Y. Kolotkov; V. V. Smirnova; P. V. Strekalova; A. Riehokainen; V. M. Nakariakov (EDP SCIENCES S A, 2022)
Aims. Long-period quasi-periodic variations of the average magnetic field in a small-scale magnetic structure on the Sun are analysed. The structure is situated at the photospheric level and is involved in a facula formation in the chromosphere.Methods. The observational signal obtained from the SDO/HMI line-of-sight magnetograms of the target structure has a non-stationary behaviour, and is therefore processed with the Hilbert-Huang Transform spectral technique.Results. The empirical decomposition of the original signal and subsequent testing of the statistical significance of its intrinsic modes reveal the presence of the white and pink noisy components for the periods shorter and longer than 10 min, respectively, and a significant oscillatory mode. The oscillation is found to have a non-stationary period growing from approximately 80 to 230 min and an increasing relative amplitude, while the mean magnetic field in the oscillating structure is seen to decrease. The observed behaviour could be interpreted either by the dynamical interaction of the structure with the boundaries of supergranula cells in the region of interest or in terms of the vortex shedding appearing during the magnetic flux emergence.